Pro Android Games: L Edition - Nardone, Massimo (Springer, 2015)
Combining actionable, real-world source code with graphics, Pro Android Games, Third Edition shows you how to build more sophisticated and addictive Android game apps with minimum effort. Harness the power of the latest Android 5.0 SDK to bring countless legendary, action-packed PC games to the Android platform.